Poligami dalam Perspektif Tafsir Maqāṣid Ibnu Asyur: Telaah atas QS. An-Nisā’ Ayat 3 dan Relevansinya bagi Keluarga Kontemporer - Afdhal Fikri; M Wildan Fauzbika (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study examines Ibn Ashur's interpretation of the maqasid (objectives) of the verse on polygamy in Surah An-Nisa verse 3 and its relevance to contemporary family dynamics. In the context of Islamic law, polygamy is often understood as an absolute right, even though normatively the Qur'an requires justice as the main principle, which is very difficult to achieve in practice. Through the maqasid al-syari'ah approach, Ibn Ashur interprets the permissibility of polygamy as a conditional form of rukhshah aimed at protecting vulnerable groups, such as orphans and women who have lost protection after war. This study uses a qualitative method with a literature review and content analysis of the tafsir al-Tahrir wa al-Tanwir. The results show that the practice of polygamy that does not consider the principles of maqashid, such as justice, protection of life, family stability, and social welfare, has the potential to cause family dysfunction, emotional instability, and social and economic crises. Ibn Ashur's maqasid interpretation offers a more ethical, contextual, and relevant approach in responding to the practice of polygamy in the modern era, as well as being an important reference in the renewal of Islamic family law that is just and beneficial. Based on these findings, it is recommended that the maqasid al-syari'ah approach be integrated into the formulation of Islamic legal policies and religious education curricula to ensure that the practice of polygamy is carried out proportionally and responsibly. Religious institutions and educational institutions are also expected to take a strategic role in building a contextual understanding of legal verses in order to avoid textual interpretations that have the potential to harm vulnerable parties